"A Latter-Day Hitler": Anti-Shah Activism and British Policy towards Iran, 1974-1976. Issue 3 (3rd July 2019) - Felci, Vittorio
ABSTRACT: This analysis examines the foreign policy features and domestic implications of British policy towards Iran between 1974 and 1976. Starting with the assumption that economic interests, as well as Cold War imperatives, shaped British policy towards Iran into one where human rights had no space, the conduct of Britain's foreign policy apparatus towards the Shah vis à vis the disturbing reporting of human rights abuses in Iran and the intensification of anti-Shah activism in Britain remains important. Situating the relationship amongst societal forces, foreign policy, and diplomacy as the main analytical thread, this analysis brings new evidence to the field of Britain's relations with Iran, anti-Shah activism abroad, and the effects of the government's policy towards Iran on the British Labour Party.